Evaluation of Aperiodic Control for Energy Saving in Wireless Networked Control Systems - Andrade, Yuri S. [UNESP]; Mansano, Raul K. [UNESP]; Godoy, Eduardo P. [UNESP]; Porto, Arthur J. V.; IEEE (Ieee, 2016)
A recent trend has been on the use of wireless networks in network control systems (NCS). One of the main challenges related to wireless networked control systems (WNCS) concerns the energy efficiency of the devices. As batteries power the wireless sensors, the lowest possible consumption is required to extend battery lifetime. In this paper, aperiodic control strategies for WNCSs were designed to handle this problem. Aperiodic control are control systems that do not require the periodic transmission of the process variable and calculated control signals. The aperiodic control designed extends the PIDPlus controller usage with an aperiodic sampling trigger based on the information of the WNCS output error. Experimental results in a WNCS testbed prove that aperiodic control strategies can considerably reduce the wireless sensor transmissions, saving their battery lifetime, without decreasing the WNCS control performance. A comparison is presented to investigate which aperiodic algorithm provides the best balance between the WNCS control performance and the number of wireless transmissions. Additionally, an optimization graph is proposed to achieve an energy efficient control for the WNCS, i.e. the best control performance with the smallest number of wireless transmissions (energy expenditure) for the WNCS operating with the aperiodic control.
Keywords: PIDPlus; Energy Efficiency; Event based control